2022
DOI: 10.1007/s10483-022-2934-6
|View full text |Cite
|
Sign up to set email alerts
|

NES cell

Abstract: A broadband adaptive vibration control strategy with high reliability and flexible versatility is proposed. The high vibration damping performance of nonlinear energy sink (NES) has attracted attention. However, targeted energy transfer may cause severe vibration of NES. Besides, it is difficult to realize pure nonlinear stiffness without the linear part. As a result, the reliability of NES is not high. The low reliability of NES has hindered its application in engineering. In addition, the performance of NES … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(5 citation statements)
references
References 41 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…Kong et al [7,8] studied the dynamics of 1-dof and 2-dof NES with geometrically nonlinear damping, the incorporation of this type of damping into the NES absorber system enhances vibration absorption signi cantly. Several traditional cubic NESs can be integrated in series [9][10][11] or parallel [12][13][14][15] in order to optimize the vibration absorption capabilities, and it was revealed that they exhibit superior performance when compared to single-degree-of-freedom (SDOF) NESs of equal mass. However, the ability of NES to absorb vibration can also be greatly affected by variations in its initial energy, and may even fail under excessive input energy that forms a frequency island.…”
Section: Introductionmentioning
confidence: 99%
“…Kong et al [7,8] studied the dynamics of 1-dof and 2-dof NES with geometrically nonlinear damping, the incorporation of this type of damping into the NES absorber system enhances vibration absorption signi cantly. Several traditional cubic NESs can be integrated in series [9][10][11] or parallel [12][13][14][15] in order to optimize the vibration absorption capabilities, and it was revealed that they exhibit superior performance when compared to single-degree-of-freedom (SDOF) NESs of equal mass. However, the ability of NES to absorb vibration can also be greatly affected by variations in its initial energy, and may even fail under excessive input energy that forms a frequency island.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many scholars have studied and extended the applications of NESs [26][27][28] , and many types of NESs have been proposed, e.g., limited NESs [29][30][31] , inertial NESs [32][33] , lever-type NESs [34] , multi-stable NESs [21,35] , track NESs (TNESs) [36][37] , and NES cells [38] . In addition, many research methods and experiments have been developed to evaluate the vibration control effect of NESs.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Some scholars have explored the possibility of achieving enhanced vibration reduction by increasing the number of NES units. [15] Ding et al [16] firstly put forward the concept of NES cell and have improved the reliability of NES and its versatility to complex vibration structures by adding a large number of NES cells in parallel. Additionally, considerable attention has been devoted to studying the dynamic response of systems coupled with NESs under conditions of random or harmonic excitation.…”
Section: Introductionmentioning
confidence: 99%